2018
DOI: 10.1177/0883073818774960
|View full text |Cite
|
Sign up to set email alerts
|

Validating an Algorithm to Identify Patients With Infantile Spasms Using Medical Claims

Abstract: An infantile spasm is a brief seizure type that is characteristic of West syndrome. Many infants present with infantile spasms between 3-12 months of age. Early diagnosis and proper treatment of patients with infantile spasms can lead to improved clinical outcomes. However, proper identification of these patients using claims data with validation has not been performed. The authors developed and tested several algorithms using claims data. Claims data consisted of using International Classification of Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…As reported by Hussain et al [100] in a study carried out in 100 patients with ISs the treatment was started only after more than a week from the onset of the first clinical manifestations with a median time of delay of treatment of 24.5 days. Wang et al [101] developed an algorithm using medical claims data at the aim to properly and early identify the ES.…”
Section: Clinical Features Seizure Types and Eeg Featuresmentioning
confidence: 99%
“…As reported by Hussain et al [100] in a study carried out in 100 patients with ISs the treatment was started only after more than a week from the onset of the first clinical manifestations with a median time of delay of treatment of 24.5 days. Wang et al [101] developed an algorithm using medical claims data at the aim to properly and early identify the ES.…”
Section: Clinical Features Seizure Types and Eeg Featuresmentioning
confidence: 99%
“…The use of ICD code alone performed the best. 3 Similarly, Reid et al showed ICD-9 and ICD-10 codes were both sensitive (89%) and specific (92%) for adult patients with epilepsy. One study used diagnosis codes from a Medicaid multi-state database to identify patients with Lennox-Gastaut syndrome (LGS) but the database did not contain complete clinical information, limiting the authors' ability to validate the data.…”
Section: Prior Literaturementioning
confidence: 94%
“…From PHIS, we identified all patients with an International Classification of Diseases, Ninth Revision, Clinical Modifications (ICD-9) code indicative of infantile spasms (ICD-9-CM: 345.6, 345.60, 345.61), from January 1, 2004 to September 30, 2015. Prior work has indicated the effectiveness of using ICD codes for identifying patients with IS ( 8 ). Outcomes for each patient were measured for up to five years after initial IS diagnosis.…”
Section: Methodsmentioning
confidence: 99%